Pengaruh Pengembangan Model Discovery Learning terhadap Kemampuan Koneksi Matematika Mahasiswa dalam Pembelajaran Online Matematika Ekonomi - Listyotami, Mega Kusuma; Ferita, Rolina Amriyanti (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
The research aims to determine the influence of developing a discovery learning model on students' mathematical connection abilities in online mathematics and economics learning. This research was conducted at the Dwi Sakti Baturaja College of Economics. The research method used in this research is pre-experiment with a One Group Pretest-Posttest Design research design. The sample for this research consisted of 30 students. Data collection techniques use test techniques which are divided into pretest and posttest. The data processing technique uses t-test calculations with the SPSS 20 program. The research results show the influence of developing a discovery learning model on increasing students' mathematical connection abilities in online mathematics and economics courses at the Dwi Sakti Baturaja College of Economics. The average initial test score was 48.50, increasing from 37.00 to 85.50 in the final test. The test results show that the t count is 17.796 and the t-table (df 30 = 2.048). The t-count value (17.796)t-table (2.048). The results show that Ho is rejected and Ha is accepted. Thus, it can be said that the development of the discovery learning model influences students' mathematical connection abilities in online mathematics and economics learning. The results of the analysis show that the R square value of the correlation analysis between the development of the discovery learning model on students' mathematical connection abilities in online learning for mathematics economics courses is 71.50%, which means that the contribution of developing the discovery learning model has a positive influence on students' mathematical connection abilities in online learning mathematics economy.